Churn and loyalty behaviour of Turkish digital natives - Faruk Guven (International Telecommunications Society (ITS), 2018)
The mobile industry drives innovation and economic growth all over the world, thanks to the application industry, content providers and mobile handset producers and operators. With a very young and dynamic population and a remarkable 96 percent mobile penetration rate, Turkey is no stranger to this trend. Yes, this very segment – commonly referred to as digital natives – also poses a dilemma for telecom operators: a high rate of attrition or the churn phenomenon. This paper reports on an empirical examination of the churn and loyalty characteristics of digital natives in the Turkish context. We employ a large sample of youth and analyse their churn and loyalty likelihoods. Overall, we find convincing evidence that, by having a consumer-centric approach and knowing more about their individual customers, telecom operators can drive loyalty and prevent churn. The rise of big data and sophisticated analysis based on behavioral patterns implies that operators now have the tools they need to predict consumer behavior better than ever before.
Keywords: 330; Digital Natives; Churn; Loyalty; Consumer Behavior; Turkey; Mobile Services